Pituitary-adrenal dysfunction caused by nivolumab for head and neck cancer. Issue 6 (December 2019) - Hihara, Kosuke; Sato, Hiroki; Okamoto, Isaku; Katsube, Yasuaki; Maruyama, Ryo; Tomioka, Ryota; Tanaka, Hideki; Tsukahara, Kiyoaki
Abstract: Nivolumab exerts antitumor effects by inhibiting binding of PD-L1 to PD-1, and offers proven effectiveness in various disease areas, including cancers of the head and neck. The mechanisms of action lead nivolumab to induce immune-related adverse events (irAE). We report a case of pituitary-adrenal dysfunction to isolated adrenocorticotropic hormone (ACTH) deficiency as an irAE of nivolumab in a patient treated for head and neck cancer. This is the first report of an irAE of nivolumab in the field of head and neck squamous cell cancer. The patient was a man in his 50s with cancer of the tongue and hypopharynx that recurred after chemoradiotherapy, surgery and chemotherapy. After starting nivolumab, irAEs developed after 8 courses. The case was managed from the early stages in collaboration with the endocrinology department. Pituitary-adrenal hypofunction due to isolated ACTH deficiency was diagnosed on the basis of endocrine tests. The patient responded to hydrocortisone replacement therapy and has been able to continue treatment with nivolumab while continuing oral hydrocortisone. Although irAEs involving pituitary gland disorders are rare, these events can become life-threatening when severe. Early diagnosis and treatment are essential and require regular blood sampling and collaboration with specialists from an early stage.